1978
DOI: 10.1084/jem.147.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific T-cell-mediated suppression. I. Induction of L-glutamic acid(60)-L-alanine(30)-L-tyrosine(10) specific suppressor T cells in vitro requires both antigen-specific T-cell-suppressor factor and antigen

Abstract: A combination of in vitro and in vivo techniques were used to explore the mode of action of both crude and purified suppressive extracts specific for the random copolymer L-giutamic acid(60)-L-alanine(30)-L-tyrosine(10) (GAT- T(s)F) obtained from nonresponder DBA/1 (H-2(q)) mice. Normal DBA/1 spleen cells were incubated under modified Mishell-Dutton culture conditions for 2 days together with crude or purified GAT-T(s)F, and in the presence or absence of free GAT. These cells were then washed extensively and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

1978
1978
1988
1988

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 28 publications
4
37
1
Order By: Relevance
“…Indirect evidence against this possibility has been obtained by Th~ze et One mechanism by which GAT-TsF suppresses GAT-MBSA PFC responses is by stimulation of GAT-Ts cells in the recipient (10). In addition, crude extracts containing GAT complexed to GAT-TsF stimulates GAT-Ts cells in recipient mice whereas purified GAT-TsF containing no detectable GAT does not (11). Furthermore, the addition of small amounts of GAT, in concentrations too low to stimulate Ts cells independently, to purified GAT-TsF restores the capacity to stimulate GAT-Ts cells (11).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Indirect evidence against this possibility has been obtained by Th~ze et One mechanism by which GAT-TsF suppresses GAT-MBSA PFC responses is by stimulation of GAT-Ts cells in the recipient (10). In addition, crude extracts containing GAT complexed to GAT-TsF stimulates GAT-Ts cells in recipient mice whereas purified GAT-TsF containing no detectable GAT does not (11). Furthermore, the addition of small amounts of GAT, in concentrations too low to stimulate Ts cells independently, to purified GAT-TsF restores the capacity to stimulate GAT-Ts cells (11).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, crude extracts containing GAT complexed to GAT-TsF stimulates GAT-Ts cells in recipient mice whereas purified GAT-TsF containing no detectable GAT does not (11). Furthermore, the addition of small amounts of GAT, in concentrations too low to stimulate Ts cells independently, to purified GAT-TsF restores the capacity to stimulate GAT-Ts cells (11). This observation raised the possibility that GATTsF complexed to a fragment of GAT (as it is found in crude extracts) might suppress across histocompatibility barriers by virtue of stimulating autologous GAT-Ts cells in the recipient and thereby masking potential restrictions between donors and recipients.…”
Section: Discussionmentioning
confidence: 99%
“…SF in many cases bear antigen-specific recognition units (5,7,8,19,20), are proteins derived from the suppressor T cell (5, 9), bear determinants encoded by the I-J subregion of the H-2 MHC (5,6,8,22), and do not bear conventional determinants present on Ig light or heavy chains constant regions (5,7,19). The potential mechanisms by which SF manifests suppression include the stimulation and generation of second-order suppressor T cells in as yet an incompletely understood manner (23,24) and/or alternatively, the direct inactivation of T helper (23) or T-effector cells (20).…”
Section: Aba-celt Induced Suppressor T-cells-derived-suppressor Factomentioning
confidence: 99%
“…The treated cells were also enriched for IgM and IgG anti-SRBC PFC. Finally, experimental conditions were then chosen to use a treatment with anti-H-2 antiserum and complement to selectively eliminate the sIg-cells in educated The initial purpose of these experiments was to obtain a soluble factor from T cells that might induce T~ in analogy with the GAT system (13). Therefore, the in vitro SRBC-education protocol developed by Eardley and Gershon (16) was followed in an attempt to generate an SRBC-specific T~ source from which to prepare T~F.…”
Section: Sig+-educated Cells Are Responsible For Suppressionmentioning
confidence: 99%
“…Previous data have shown that Ts play a major role in the regulation of the Ir gene-controlled response to L-glutamic acid6°-L-alaninea°-L-tyrosine l° (GAT): GAT priming of nonresponder mice leads primarily to stimulation of GAT-specific T~ (11), which produce a soluble GAT TsF factor (GAT-TsF) (9) bearing I-region determinants and sharing a common idiotype with anti-GAT antibodies (12) that stimulates virgin T cells to develop T~ activity (GAT-T+F-induced Ts [T~]) (13). Furthermore, similar T~ and T+F can be obtained from responder lymphocytes, provided that antigen-presenting adherent cells are removed before GAT exposure (14).…”
mentioning
confidence: 99%